Turnover Intention of Generation Z in Banking Industries: A Literature Review - Kirana, Nanda Wahyu Indah; Sunani, Avi; Wanti, Ulfa Puspa; Lukitasari, Ika Chandra (Nusantara Science and Technology Proceedings, 2023)
Turnover Intention is closely related to the subjective prospect of an employee of a company to move and leave his job in search of another opportunity in a different place. The high assumption of workers in shifting jobs is influenced by the high expectations of gaining an advantage over other companies. Generation Z or the Society born above 1998 has a basic character that wants to explore something new and uncomfortable when working under pressure. Generation Z will be a potential and valuable talent for “Golden Indonesia”, and will be a lot of economic reinforcement in it. The sector that will strengthen the economy is banking. This research will discuss comprehensively the generation that will occupy the peak of the economy in “Golden Indonesia” with the literature review approach previously studied. This research was conducted to study and prevent a large number of Z generations in the banking environment from having a tendency to turnover intention. This study reveals that turnover intention is influenced by some factors, such as work environment, job competency, and job satisfaction. Thus, in order to prevent the level of turnover intention, the company should consider those factors. Satisfaction with good workplace support will greatly affect the generation that is unstable to survive the plethora of strong lifestyle competition tendencies that color Generation Z in world progress, in economics.